A new polymorphism for the RI22H mutation in hereditary pancreatitis. Issue 2 (1st February 2001) - Howes, N; Greenhalf, W; Rutherford, S; O'Donnell, M; Mountford, R; Ellis, I; Whitcomb, D; Imrie, C; Drumm, B; Neoptolemos, J P
Abstract : BACKGROUND AND AIMS: Hereditary pancreatitis (HP) is a rare form of recurrent acute and chronic pancreatitis. Mutations in the cationic trypsinogen (protease serine 1, PRSS1) gene have been identified as causing HP. The R122H (previously known as R117H) mutation is the commonest and can be detected by a single and rapid polymerase chain reaction/restriction fragment length polymorphism (PCR/RFLP) based technique using the Afl III enzyme. This test however may give a false negative result in the presence of a neutral polymorphism within the enzyme recognition site. The frequency of this event was examined by sequencing studies in patients with HP and in healthy controls. METHODS: Of 60 families identified by the UK and Ireland consortium of EUROPAC (European Registry for Hereditary Pancreatitis and Familial Pancreatic Cancer), 51 were screened for R122H, N29I, and A16V mutations using standard techniques, and by sequencing of all five exons of cationic trypsinogen. RESULTS: Twelve families had the N29I mutation, one family had A16V and, on standard testing, 15 families had the R122H mutation. An additional family with the R122H mutation was found on direct sequencing. The false negative result was due to a neutral polymorphism C→T at the third base of the codon, not affecting the amino acid coded for, destroying the Afl III restriction site. This polymorphism was not observed in 50 DNA specimens (100 chromosomes) from controls nor from 50 individuals from PRSS1 mutation negative HP families. A novel mutation specific PCR was developed to avoid this pitfall. CONCLUSIONS: One of the 16 families with HP and an R122H mutation contained a polymorphism affecting the Afl III restriction site. Adoption of an alternative R122H assay is important for genetic studies in individuals with apparent HP.